Analisis Faktor-Faktor yang Memengaruhi Kepercayaan Pengguna Dalam Menggunakan Aplikasi Al-Quran Mobile XYZ Menggunakan Model Modified UTAUT - Muhammad Nurul Fanani; Ari Kusyanti; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Al-Quran Mobile XYZ is a mobile al-quran application based on android and ios. Al-Quran Mobile XYZ counted as many as 10 million downloads through the play store. It shows how much the public interest to use the application of Al-Quran Mobile. With the presence of Al-Quran Mobile XYZ applications users do not need to carry the Quran manuscripts everywhere, only with smartphone users can easily carry and read anytime. But it would be a problem if the user does not pay attention to verses of the Quran that turned out to be an error. There have been several cases that have occurred with regard to errors in al-quran verses in one of the available applications, but still many users continue to use mobile al-quran applications. In this research, the research method used is Unified Teory of Acceptance and Use of Technology (UTAUT), UTAUT Model shows that intention to behave (behavioral intention) is influenced by performance expectancy, effort expectancy, social influence, and facilitating conditions. Also in this research model is also combined with other factors, such as trust, perceived risk, and perceived information quality. This study used a sample of 100 respondents refers to the slovin formula. Then for the method of analysis using path analysis. The results show that perceived information quality has significant influence on trust, and facilitating conditions have a significant effect on behavioral intention.